PEMETAAN RUMAH MAKAN LESEHAN DI KECAMATAN SELONG DAN MASBAGIK KABUPATEN LOMBOK TIMUR BERBASIS GIS (GEOGRAPHIC INFORMATION SYSTEM) - nur, amri muliawan; Mahpuz, Mahpuz (Fakultas Teknik Universitas Hamzanwadi, 2020)
Geographic Information System (GIS) is a web-based information system that is used to process and store geographic-based information. This study aims to produce a geographic information system with a visualization that contains the location of Lesehan restaurants in Selong and Masbagik sub-districts, Restaurant information containing instructions and directions to Lesbian Restaurant. The data used in this research is to collect map data in selong and masbagik districts using the Google Map API and Google Map Direction Service, coordinate data collection points and some other supporting data. The result of this research is that a geographic information system web site in Selong and Masbagik District based on web has been built using a web-based Google Maps API that makes it easy for web users to find out the position of Lesbian restaurants, where there is information on Lesbian restaurants, positions lesehan restaurant, directions to the desired lesehan restaurant.DOI : 10.29408/jit.v3i1.1803